Peningkatan Kompetensi Guru SDN Kalirungkut 1 Surabaya dalam Penyusunan Modul Ajar Berdiferensiasi dan Berbasis Proyek P-5 untuk Menanamkan Karakter Rahmatan lil Alamin [Enhancing the Competence of SDN Kalirungkut 1 Surabaya Teachers in Developing Differentiated and Project-Based P-5 Teaching Modules to Instill the Rahmatan lil Alamin Character] - Ghufron, Syamsul; Nafiah, Nafiah; Susanto, Rudi Umar; Kasiyun, Suharmono; Saputri, Tiyas (Indonesia Berdaya, 2025)
Abstract. The community service program conducted at SDN Kalirungkut 1 Surabaya aimed to improve teachers' competence in designing differentiated and project-based P-5 learning that integrates the Rahmatan lil Alamin character. The program was implemented through a five-day training and mentoring session, focusing on developing teaching modules tailored to students' needs and characteristics, as well as instilling values such as kindness, tolerance, and empathy. The results of the training demonstrated a significant improvement in teachers' understanding and skills in designing more inclusive and character-based learning. The sustainability of the program is ensured through ongoing mentoring and strengthened collaboration among teachers. Abstrak. Pengabdian masyarakat yang dilaksanakan di SDN Kalirungkut 1 Surabaya bertujuan untuk meningkatkan kompetensi guru dalam merancang pembelajaran berdiferensiasi dan berbasis proyek P-5 yang mengintegrasikan karakter Rahmatan lil Alamin. Program ini dilaksanakan melalui pelatihan dan pendampingan selama lima hari, dengan fokus pada pengembangan modul ajar yang sesuai dengan kebutuhan dan karakteristik siswa, serta penanaman nilai karakter seperti kasih sayang, toleransi, dan empati. Hasil dari pelatihan ini menunjukkan peningkatan signifikan dalam pemahaman dan keterampilan guru dalam merancang pembelajaran yang lebih inklusif dan berkarakter. Keberlanjutan program dijamin melalui pendampingan berkelanjutan dan penguatan kolaborasi antar guru.